Resettlement, household vulnerability, livelihood adaptation and opportunities in Ethiopia : a case study of the Metema resettlement area - Bahry, Mihret Jember (University of Cape Town, 2015)
Includes abstract. === Includes bibliographical references (leaves 137-152). === This thesis examines the recent experience of resettlement through a case-study of the Metema Woreda resettlement site, located in the Amhara Regional State from a disaster risk lens through the application of the sustainable livelihoods framework. Specifically, the study sought to examine the vulnerability and risk context of resettled households. It also aimed to investigate the ways in which household livelihoods are configured and differentiated in the new environment.